Transferibilidade de microssatélites de cactáceas para a análise de regenerantes clonais (R0) de Cereus peruvianus Mill. (Cactaceae) - Martin, Paula Garcia (2011)
Due to the growing economical and industrial importance of the cactus species Cereus peruvianus, the purpose of the present work was to exam the transferability of SSR markers developed from genomes of different species of cactus to the C. peruvianus plants, as a way to determine the genetic diversity and analyze the structure of somaclones populations generated in vitro that show somaclonal variation. 33 pairs of microsatellites primers developed for different species of cactus were evaluated. From this evaluation, 9 primers were selected, giving a transferability of 27, 27% from these primers to C.peruvianus. The evaluated loci showed 23 alleles, with a medium of 2,56 alleles pre polymorphic locus. The morphological somaclonal variants (atypical stems) of C.peruvianus show less diversity of alleles and heterozygous genotypes. The mEgR76, mAbR28, Pchi47, mEgR78, mEgR02, Pchi54, e mAbR42 loci were considered effective to analyse the genetic diversity and the population structure of C. peruvianus; and the mEgR76 e mAbR77, mEgR02, e mAbR28 loci were indicated to investigate morphological differences in the stems of Mandacaru plants of the Cereus genus or in C. peruvianusvarieties with altered morphology of stems found in the wild. The genetic identity level observed (0,8836 ? 0,9609) among the somaclones with typical, atypical and mixed stems indicated that the plants with atypical stems can be considered as being from the same species of the somaclones with typical stems.